2006
DOI: 10.1073/pnas.0604476103
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of full-round uridine-deletion RNA editing with three recombinant proteins

Abstract: Uridine (U)-insertion͞deletion RNA editing in trypanosome mitochondria involves an initial cleavage of the preedited mRNA at specific sites determined by the annealing of partially complementary guide RNAs. An involvement of two RNase III-containing core editing complex (L-complex) proteins, MP90 (KREPB1) and MP61 (KREPB3) in, respectively, U-deletion and U-insertion editing, has been suggested, but these putative enzymes have not been characterized or expressed in active form. Recombinant MP90 proteins from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 43 publications
(55 reference statements)
0
43
0
Order By: Relevance
“…4A), indicating that TbMP42 is needed for any cleavage by the TbMP90 endonuclease in trypanosome extracts. (However, studies using recombinant proteins have shown that rTbMP90 cleaves an editing site in the presence of rTbMP63, without rTbMP42 [Kang et al 2006], suggesting that in vivo TbMP42 likely serves to retain the presence of the active TbMP90.) In contrast to its effects on the U-deletional endonuclease, depletion of TbMP42 (at 3 d of RNAi induction) does not affect the basic cleavage activity of the U-insertional endonuclease (Fig.…”
Section: Tbmp42 Is Needed Formentioning
confidence: 99%
See 3 more Smart Citations
“…4A), indicating that TbMP42 is needed for any cleavage by the TbMP90 endonuclease in trypanosome extracts. (However, studies using recombinant proteins have shown that rTbMP90 cleaves an editing site in the presence of rTbMP63, without rTbMP42 [Kang et al 2006], suggesting that in vivo TbMP42 likely serves to retain the presence of the active TbMP90.) In contrast to its effects on the U-deletional endonuclease, depletion of TbMP42 (at 3 d of RNAi induction) does not affect the basic cleavage activity of the U-insertional endonuclease (Fig.…”
Section: Tbmp42 Is Needed Formentioning
confidence: 99%
“…In some references, the initial ''K'' is omitted, and, additionally, TbMP52 has also been referred to as DREL (Cruz-Reyes et al 2002) and TbMP48 as IREL (Cruz-Reyes et al 2002). Purification of editing complexes from L. tarentolae yields many homologous proteins, initially named LmLC# ) then shortened to LC# (Kang et al 2006). For uniformity with the bulk of the editing literature, after their initial mention, we use the TbMP# designation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mRNAs are edited at over a hundred sites, and at each site, editing starts by a nuclease cleavage directed by a complementary gRNA (Rusche et al 1997;Stuart et al 2005;Li et al 2009;Simpson et al 2010). There are three accepted specialized editing endonucleases, REN1, REN2, and REN3 Trotter et al 2005;Kang et al 2006;Simpson et al 2010), although only REN1 has been produced in an active recombinant form (Kang et al 2006). RENs have a conserved RNase III domain and two domains of unknown function (Worthey et al 2003).…”
Section: Introductionmentioning
confidence: 99%